2022
DOI: 10.1001/jamanetworkopen.2022.15000
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Studies Comparing Structured vs Nonstructured Diagnostic Protocol Evaluations Among Patients With Fever of Unknown Origin

Abstract: This systematic review and meta-analysis compares diagnostic yield studies using a structured or a nonstructured diagnostic approach to treating patients with fever of unknown origin syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
(188 reference statements)
0
10
0
Order By: Relevance
“…Outcome measures have been the preferred approach for developing quality infectious disease indicators because process measures are not always a perfectly mapped surrogate for the desired result, particularly among conditions with significant heterogeneity such as FUO and IUO [ 2 , 12 ]. For example, educating clinicians on utilizing protocolized (algorithmic) FUO or IUO diagnostic evaluations does not necessarily result in the reduction of patients remaining undiagnosed, nor is physician education the only way to improve achieving a diagnosis [ 13 ]. Outcome measures can also be supplemented with statistical methods, such as stratification or risk adjustment, that control for factors that influence the relationship between a predictor and outcome that is often out of the clinician's control [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Outcome measures have been the preferred approach for developing quality infectious disease indicators because process measures are not always a perfectly mapped surrogate for the desired result, particularly among conditions with significant heterogeneity such as FUO and IUO [ 2 , 12 ]. For example, educating clinicians on utilizing protocolized (algorithmic) FUO or IUO diagnostic evaluations does not necessarily result in the reduction of patients remaining undiagnosed, nor is physician education the only way to improve achieving a diagnosis [ 13 ]. Outcome measures can also be supplemented with statistical methods, such as stratification or risk adjustment, that control for factors that influence the relationship between a predictor and outcome that is often out of the clinician's control [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…FUO and IUO are conditions without defined optimal evaluation and management strategies [ 5 , 13 ]. To date, no high-quality randomized controlled trials have been performed [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite diagnostic advances, it has been reported that in high-income countries half of the cases of FUO and IUO remain undiagnosed [ 96 , 105 ]. According to a recent study, diagnostic evaluation of FUO and IUO should be based on local disease prevalence, and individual presentations [ 106 ].…”
Section: Fever Of Unknown Origin (Fuo) and Inflammation Of Unknown Or...mentioning
confidence: 99%
“…Advances in clinical research and diagnostic testing methods over the last 3 decades suggest that an update for existing definitions and approaches for fever and inflammation of unknown origin is needed [ 1–4 ]. Classic fever of unknown origin (FUO) was first robustly studied in 1961, with subsequent modifications in definitions ( Table 1 ) [ 1 , 2 ]. These FUO definitions require an illness of ≥3 weeks duration and temperatures of ≥38.3°C (≥100.9°F) on several occasions [ 1 , 2 ].…”
mentioning
confidence: 99%